TINJAUAN PENGGUNAAN KOMPUTER TERKAIT GEJALA COMPUTER VISION SYNDROME (CVS) PADA PETUGAS REKAM MEDIS DI RUMAH SAKIT X KEDIRI TAHUN 2023 - Christabella Nafthalia Wardhani; Ni’matu Zuliana; Deni Luvi Jayanto; Krisnita Dwi Jayanti; Adi Laksono (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
Information technology is currently developing very rapidly. The development of this technology is evidenced by the use of computers in Electronic Medical Records. Computer use can have both positive and negative impacts on its users. One of the negative impacts is Computer Vision Syndrome. The design of this research is quantitative research with descriptive method. The study population consisted of 24 medical record officers who used computers using a purposive sampling technique, with a sample of 6 officers who met the inclusion criteria. Data collection was carried out by interview and observation sheets. The results of this study found that the number of medical record officers at the X Hospital in Kediri City who were more at risk of experiencing symptoms of Computer Vision Syndrome were 6 officers with age ≤45 years, 4 officers with ≤5 years of service and 2 officers >5 years, staring at the computer monitor for a long time of the 6 officers included in the >2 hour time category, the distance between the computer monitor and the eyes of 3 officers was 45-60 cm and the other 3 officers were<45->60 cm. It is recommended that officers can blink their eyes periodically, adjust the brightness of the computer monitor, check visual acuity, take regular eye breaks according to the 20-20-20 rule and use the zoom in or zoom out technique to adjust the writing on the computer screen.